How Perceived Price and Value Affect Purchases in Ping Ping Thai Tea Business - Saraswati, Putu Diva Pradnya; Yulianti, Ida (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Understanding consumer behavior in purchasing decisions is essential for business success, particularly in the highly competitive food and beverage (F&B) industry. Ping Ping Thai Tea, a micro, small, and medium enterprise (MSME) in this sector, has faced challenges in increasing purchase decisions due to product limitations. Benchmarking against several competitors reveals two key factors influencing purchase decisions: perceived value and perceived price. This quantitative study aims to analyze the influence of perceived value and perceived price on consumer purchase decisions at Ping Ping Thai Tea. The data were collected through questionnaires distributed to 191 consumers and analyzed using multiple linear regression. The findings show that the t-value for perceived price is 2.858 with a significance value of 0.001, indicating that a higher perceived price increases purchase decisions. Similarly, the t-value for perceived value is 10.967 with a significance value of 0.005, indicating that a higher perceived value also increases purchase decisions. Therefore, maintaining affordable pricing can enhance perceived price, while improving service convenience can strengthen perceived value.